PENGARUH PIJAT OKSITOSIN TERHADAP LAMA PERSALINAN KALA I FASE AKTIF DI KLINIK PIM KOTA DEPOK TAHUN 2021 - Saleha, Sitti; Sulastriningsih, Kursih (Ikatan Bidan Indonesia (IBI), 2022)
Background: The other causes of maternal deaths In West Java Province, 19.74%, one of which was due to prolonged labor. One way to speed up the progress of labor is by giving oxytocin massage. The purpose of the study was to knowing the effect of oxytocin massage on the duration of the active phase of the first stage of labor at the Ismail Medika Inpatient Pratama Clinic, Depok Period March-April 2021. Methods: quasi-experimental research design using a posttest only design with control groups. The sample in this study amounted to 30 mothers giving birth with each group consisting of 15 respondents with purposive sampling technique. The data were analyzed using the Mann-Whitney test which was previously tested for normality. Result: univariate analysis of the duration of labor in the first active phase of the intervention group was mostly normal 86.7%, the control group was mostly 66.7%. The results of the bivariate analysis showed that there was an effect of oxytocin massage on the duration of the first stage of labor in the active phase with a significance value of 0.000. The conclusion of this research is oxytocin massage affects the duration of the active phase of the first stage of labor. Suggestions for midwives are expected to be able to assist maternity mothers in meeting the mother's need for comfort in non-pharmacological pain control when providing delivery care by applying the oxytocin massage technique so that labor can run effectively and safely both in terms of the length of labor and the condition of the baby being born.